Performance Effects of Different Audit Staff Assignment Strategies. - Blocher, Edward (The Accounting Review, 1979)
Abstract This study examines the effect on audit staff performance of different assignment strategies. There is a review of the theoretical models and related empirical evidence for performance in a sequence of assignments, and data from 573 staff evaluation forms for two offices of large public accounting firms are analyzed. The review and analysis show some evidence that there is a lapse in performance over time for audit staff at the senior level if the seniors are assigned consecutively within a particular industry, while no lapse in performance is observed for those seniors who are rotated among assignments in different industries. These findings are generally consistent with the research findings in interference theory–a theory which attempts to explain certain kinds of verbal learning behavior.